2022
DOI: 10.7324/japs.2021.120102
|View full text |Cite
|
Sign up to set email alerts
|

Short review on the potential alternatives to antibiotics in the era of antibiotic resistance

Abstract: The importance of antibiotics in the treatment of infectious diseases of bacterial origin is well established. Despite the positive contribution of antibiotics in veterinary and clinical medicine, some of these molecules were regarded as harmful to both human and animal health with some undesirable effects. Moreover, microorganisms have developed resistance mechanisms to almost all commonly used antibiotics. Hence, there is an urgent need to find alternative ways against bacterial resistance to antibiotics whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…Antibiotic resistance is defined as the ability of a bacteria to resist the inhibitory or destructive activity of an antimicrobial to which it was not resistant [1,2]. This problem poses serious public health concerns because it negatively impacts the treatment of infections requiring antibiotics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibiotic resistance is defined as the ability of a bacteria to resist the inhibitory or destructive activity of an antimicrobial to which it was not resistant [1,2]. This problem poses serious public health concerns because it negatively impacts the treatment of infections requiring antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…A recent report from the World Health Organization (WHO) estimates that more than 730,000 deaths are directly associated with antibiotic resistance annually [3]. In addition to the increase in mortality, several researchers have reported that antibiotic resistance inevitably leads to an increase in medical expenses resulting from the failure of primary antibiotic treatments and prolonged hospitalizations [2]. No bacterial infections, including urinary tract infections (UTIs), are spared from this major public health issue.…”
Section: Introductionmentioning
confidence: 99%
“…The antifungal potential of the biosynthesized AgNPs against two pathogenic strains Candida albicans and Candida tropicalis was evaluated using the agar well diffusion method as described by Joseph et al [ 18 ]. Wells with a diameter of 8 mm were punched in potato dextrose agar medium and 100 µL of each microorganism was spread using a sterile cotton swab.…”
Section: Methodsmentioning
confidence: 99%
“…Several approaches are being pursued to address the challenge of antibiotic resistance and create new drugs with improved efficacy. These include phage therapy, probiotics, antimicrobial peptides, vaccines, nanoparticles, antibodies, cytokines and therapeutic medicinal plants (Joseph et al, 2022). Among these approaches, therapeutic medicinal plants with antimicrobial properties based on traditional medicine knowledge and practices are being explored to develop new drugs with improved pharmacological activities (Kouakou et al, 2019).…”
Section: Introductionmentioning
confidence: 99%